The Relationship Between Knowledge, Perceptions, and Subjective Norms With Adolescent Attitudes Related to Gender Equality at the Darul Huffaz Islamic Boarding School in Lampung in 2025 - Aryastuti, Nurul; Febriani, Christin; Shabrina, Hanifah; Puspitasari, Yenny (Jurnal Kesmas Jambi, 2025)
This study aimed to examine the relationship between knowledge, perceptions, and subjective norms with adolescents’ attitudes toward gender equality at Darul Huffaz Islamic Boarding School, Pesawaran Regency. A quantitative cross-sectional design was applied with a population of 450 students and a sample of 127 male and female students from grades X–XII. Data were collected through questionnaires measuring knowledge, perception, subjective norms, and attitudes toward gender equality. Spearman’s correlation test was used as the data were not normally distributed. Most students showed positive attitudes toward gender equality, especially female students. However, some male students were less supportive of women’s roles in leadership and careers. Knowledge of gender equality among students remained low due to the absence of direct education from the boarding school. Perceptions were influenced by traditional values, and subjective norms reflected limited environmental support for gender equality. Statistical analysis showed no significant relationship between knowledge and attitudes (p=0.797), while both perception and subjective norms were significantly associated with attitudes (p=0.000). The study concludes that perceptions and subjective norms are significantly related to adolescents’ attitudes toward gender equality, while knowledge is not. Students with positive perceptions and supportive subjective norms are more likely to have favorable attitudes. These findings highlight the importance of education and environmental support in shaping adolescents’ attitudes toward gender issues.